To kill a mockingbird [videorecording (DVD)] - Mulligan, Robert, 1925-2008; Peck, Gregory, 1916-2003; Badham, Mary, 1952-; Lee, Harper (Universal Home Video, 1998)
The setting is a dusty Southern town during the Depression. A white woman accuses a black man of rape. Though he is obviously innocent, the outcome of his trial is such a foregone conclusion that no lawyer will step forward to defend him--except the town's most distinguished citizen. His compassionate defense costs him many friendships but earns him the respect and admiration of his two motherless children.